Comparison of the Efficacy of Dorsal Root Ganglion Pulsed Radiofrequency for 2 Minutes versus 4 Minutes in the Treatment of Chronic Lumbosacral Radicular Pain - Gökhan Yıldız; Ezgi Can (Hitit Medical Journal)

(untitled)
Objective: Pulsed radiofrequency treatment of the dorsal root ganglion has been increasingly used to treat lumbosacral radicular pain in recent decades. However, there is no consensus in the literature regarding issues such as pulsed radiofrequency application duration. This study aimed to determine the efficacy and incidence of adverse events between 2-minute and 4-minute pulsed radiofrequency for lumbosacral radicular pain. Material and Method: This retrospective study included 160 patients who underwent 2-minute or 4-minute dorsal root ganglion pulsed radiofrequency treatment (Group-2 minutes 82 patients and Group-4 minutes 78 patients). The Numeric Rating Scale and Oswestry Disability Index scores before, 1 and 6 months after the interventions were evaluated to assess the effectiveness of the procedures. The rate of intervention-related adverse events was determined for both durations. Results: Both the 2-minute and 4-minute procedures provided effective analgesia at 1 and 6 months compared with baseline. There was no difference in the pain scores between the two groups at the measurement times. At the 1-month follow-up, 50% or greater pain relief was achieved in 39% of patients in the 2-minute group compared to 50% in the 4-minute group, with no difference between the groups. There was no significant difference in the rate of procedure-related adverse events between the groups. Conclusion: Although a higher success rate was achieved with 4-minute pulsed radiofrequency, there was no significant difference, and both 2 and 4-minute pulsed radiofrequency procedures provided safe and effective analgesia compared with baseline. Prospective studies with larger sample sizes are needed.